KONSEKUENSI HEDONIC DAN UTILITARIAN VALUE: STUDI PADA ONLINE FASHION RETAILER - Sofiya Sofiya; Ayu Ekasari (EBID: Ekonomi Bisnis Digital, 2024)
This study aims to analyze the consequences of hedonic value and utilitarian value for consumers who shop at online fashion retailers. In this study, there are four variables used, namely hedonic value, utilitarian value, customer satisfaction, and behavioral intention. The analysis method used in this study uses structural equation modeling (SEM) with the number of samples used as many as 250 respondents. The sampling method in this study was purposive sampling, namely those who have bought fashion from four brands at online fashion retailers. The results of this study are (1) there is no positive influence of hedonic value on customer satisfaction (2) there is a positive influence of utilitarian value on customer satisfaction (3) there is a positive influence of hedonic value on behavioral intention (4) there is a positive influence of utilitarian value on behavioral intention (5) there is no positive influence of hedonic value on behavioral intention mediated by customer satisfaction (6) there is a positive influence of utilitarian value on behavioral intention mediated by customer satisfaction. The results of this study also provide advice to online fashion retailer brand managers so that they can develop strategies that can increase customer satisfaction.